Understanding the adsorption behavior of small molecule in MoS2 device based on first-principles calculations. (26th May 2021) - Jiang, Wenfeng; Chen, Kaifei; Wang, Jiawei; Geng, Di; Lu, Nianduan; Li, Ling
Abstract: Although layered MoS2 has been proposed as a potential candidate for gas detection devices due to high surface-to-volume ratio, high sensitivity, and selectivity, the adsorption behavior of small molecules is still ambiguous. Here, we performed the first-principles calculations to investigate the adsorption behavior of small molecules on layered MoS2 surface, and the effects of defects and environment are considered. Our results reveal that NO and NO2 can be chemically adsorbed on defective monolayer MoS2, which is attributed to the forming of covalent bonds. And the forming of covalent bonds can lead to an increase in adsorption energies. Whereas, gas molecules can only be physically adsorbed on perfect MoS2 . Meanwhile, as compared with adsorption behavior of NH3, NO, and NO2 on clean MoS2, the environmental gases (CO2, N2, and H2 O) may result in an increase in adsorption strength of NH3, NO, and NO2 on MoS2 surface.